DAMPAK TEKNOLOGI DIGITAL TERHADAP KEPEMIMPINAN NASIONAL: PELUANG DAN TANTANGAN - Rahman, Rusyda Nasyita; Agustinova, Danang Ade; Surya, Amirrudin Ardhi; Anugerah, Syah Rizal Putra (STKIP Pesisir Selatan, 2025)
This research aims to understand the influence of digital technology on national leadership by identifying opportunities, analyzing challenges, and providing recommendations for policy makers in facing changes triggered by digital transformation. This research uses a qualitative descriptive method through literature study to analyze the impact of digital technology on national leadership based on credible and relevant sources. Advances in digital technology bring significant opportunities in leadership by enhancing more effective communication, supporting transparency, and facilitating accurate, data-based decision making. These opportunities include accelerating communication in leadership, increasing transparency in government, and utilizing data for more informed decision making. On the other hand, the application of digital technology in government also faces various challenges, such as cyber security, digital access gaps between regions, as well as ethical and data privacy issues that need to be addressed to ensure the transformation is effective and inclusive. Digital technology has a significant impact on national leadership by creating opportunities such as accelerated communications, increased transparency, and data-based decision making, but also faces serious challenges such as digital access gaps, cybersecurity, and data privacy that require attention and a holistic approach.